* We will Proof that *∫ba1(x−a)(b−x)‾‾‾‾‾‾‾‾‾‾‾‾‾√dx=π

**by three**

*method**:***The first method:**

**let: x-a***＝(b-a)y **⇒ x**＝**(b-a)y + a **⇒ dx**＝(b-a)dy*

* b-x**＝b-(b-a)y-a **⇒ b-x**＝(b-a)(1-y)*

* x**＝a **⇒ ** y**＝o , x**＝b **⇒ ** y**＝1*

* let: x *=*a cos²Ө+b sin²**Ө ⇒ x-a*=* (b-a) sin²**Ө **⇒ b-x***=(b-a) cos²***Ө*

* dx*＝*-2a sin**Ө . cos**Ө d**Ө + 2b sin**Ө . cos**Ө d**Ө **＝ (b-a)sin 2**Ө d**Ө*

* x***＝b ***⇒ *** ***Ө***＝π/2 , x**

**＝a**

*⇒*

*Ө*

*＝0*

## Comments

## Post a Comment